Cointegration analysis of the relations between macroeconomic variables and the China stock market - Yang, Jianwei (2008)
China’s stock market is an emerging market with high growing speed. The behavior of two Chinese stock exchanges should be interesting to investors in the China stock market. However, few studies have investigated the potential relations between China stock market indices and economic variables by using cointegration test.